The Compton electron beam Polarimeter for the AmPS ring - Vodinas, N. P.; de Jager, C. W.; Papadakis, N. H.; Passchier, I. (HNPS Advances in Nuclear Physics, 2020)
The longitudinal polarization of the stored electron beam in the AmPS ring will be measured through the laser Compton backscattering technique. With the outlined design the measurement of the expected 70% degree of polarization to a statistical precision of 3% requires less than 60 sec under ideal conditions.